An X-ray study of the supernova remnant G20.0-0.2 and its surroundings - Petriella, Alberto (2013)
Aims. We study the supernova remnant G20.0-0.2 and its surroundings in order to look for the high energy counterpart of the radio nebula and to find evidence of interaction between the shock front and the interstellar medium. Methods. We used Chandra archival observations to analyze the X-ray emission from the supernova remnant. The surrounding gas was investigated using data extracted from the Galactic Ring Survey, the VLA Galactic Plane Survey, the Galactic Legacy Infrared Midplane Survey Extraordinaire, and the Bolocam Galactic Plane Survey. Results. G20.0-0.2 shows diffuse X-ray emission from the central region of the radio remnant. Although the current data do not allow us to distinguish between a thermal or non-thermal origin for the X-ray diffuse emission, based on the radio properties we suggest a synchrotron origin as the most favorable. The hard X-ray point source CXO J182807.4-113516 appears located at the geometrical center of the remnant and is a potential candidate to be the pulsar powering the nebula. We found a molecular cloud adjacent to the flattest border of G20.0-0.2, indicating a probable interaction between the shock front of the remnant and the molecular gas. Several young stellar object candidates are found located in the brightest region of the molecular emission, and over a millimeter continuum source and a dark cloud. This distribution is an indication of an active star forming region around the supernova remnant.